The roles of export diversification and composite country risks in carbon emissions abatement: evidence from the signatories of the regional comprehensive economic partnership agreement - Khan, Zeeshan; Murshed, Muntasir; Dong, Kangyin; Yang, Siqun (Applied economics, 2021)
The ratification of the Regional Comprehensive Economic Partnership (RCEP) agreement has laid the platform for the signatory nations to boost their respective economic growth rates, and also raised environmental concerns. So far, little is known regarding the roles of export diversification and the composite risk index in the abatement of carbon dioxide (CO 2 ) emissions for the RCEP countries. Accordingly, this study investigates the impacts of export diversification and composite risk index on CO 2 emissions for the RCEP countries between 1987 and 2017. The empirical findings indicate that lowering the composite risk index, undertaking a transition to renewable energy, and enhancing environmentally-related technological innovations help reduce CO 2 emissions in the long run. In contrast, export diversification is found to monotonically boost CO 2 emission levels. The findings also authenticate the environmental Kuznets curve (EKC) hypothesis to certify that the economic growth of the RCEP nations will be both an initial contributor and ultimate inhibitor of CO 2 emissions. In line with these findings, it is important to lower the country risk profiles of the RCEP nations, restructure the export diversification schemes, ensure technological advancement and expedite economic growth in an environmentally-friendly manner.